El Estornino Pinto (Sturnus vulgaris) en General Lavalle, Buenos Aires, Argentina - Carro, Mariana E.; Lacoretz, Mariela V.; Acosta, Tamara H. (Nuestras Aves, 2014)
Este artículo no cuenta con un resumen.